2018
DOI: 10.1021/acsenergylett.8b00607
|View full text |Cite
|
Sign up to set email alerts
|

Porphyrin Dimers as Hole-Transporting Layers for High-Efficiency and Stable Perovskite Solar Cells

Abstract: In this work, we demonstrate the optimum utilization of porphyrin-based hole-transporting materials (HTMs), namely, WT3 and YR3, for fabricating triple-cation perovskite solar cells. These newly designed HTMs based on dimeric porphyrin structure exhibit a good HOMO level, high hole mobility, and great charge extraction ability for perovskite solar cells. Moreover, through proper molecular engineering, dimeric porphyrins WT3 and YR3 are capable of forming films free of pinholes, with more uniform and dense surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(45 citation statements)
references
References 47 publications
0
42
0
Order By: Relevance
“…Recently, porphyrins, existing widely in natural organisms, have attracted much attention owning to the following reasons: 1) porphyrin ligand can be easily modified through carboxyl or phosphate groups; 2) low‐cost molecular catalyst in improving the photo‐electrochemical cell performance; 3) unique optical and electrochemical properties by modifying the peripheral substituents and metal center; 4) high hole mobility and matched energy band …”
Section: Introductionmentioning
confidence: 99%
“…Recently, porphyrins, existing widely in natural organisms, have attracted much attention owning to the following reasons: 1) porphyrin ligand can be easily modified through carboxyl or phosphate groups; 2) low‐cost molecular catalyst in improving the photo‐electrochemical cell performance; 3) unique optical and electrochemical properties by modifying the peripheral substituents and metal center; 4) high hole mobility and matched energy band …”
Section: Introductionmentioning
confidence: 99%
“…2.4 eV), and low onset potential. Meanwhile,p orphyrins can be chosen as am ediator to maximize charge utilization as compared to previously reported photosensitizers, [28] since they show relatively high hole mobility [29] and it is possible to adjust their optical and electronic properties by modifying the peripheral and nonperipheral substituents and metal center. [30] In this study,anovel interface charge modulation system was designed, and the resulting configuration (R-BV/CoPy/ FN-H, Figure 1a;h erein, reduced BiVO 4 ,5 ,10,15,20-tetrakis(4-carboxyphenyl)porphyrin-Co,a nd FeNi(OH) x are denoted as R-BV,C oPy,a nd FN-H, respectively) presented ah igh photocurrent of 4.75 mA cm À2 at 1.23 V( versus the reversible hydrogen electrode (RHE)) under AM 1.5 G illumination (100 mW cm À2 ).…”
mentioning
confidence: 99%
“…d) J – V curve and IPCE curve of WT3 device. Reproduced with permission . Copyright 2018, American Society of Chemistry.…”
Section: Htms In Conventional Structures (N–i–p)mentioning
confidence: 99%
“…Thanks to these properties, the Y2 device exhibited a high efficiency of 16.60% than the spiro‐OMeTAD device. The same group also developed dimeric porphyrins to optimize the intermolecular interaction between porphyrin molecules to enhance hole mobility . They reported that a hole‐doped conjugated dimeric porphyrin is capable of spanning a hole polaron delocalization length of 17.9 Å in contrast to 13.9 Å for a monomer in a solution.…”
Section: Htms In Conventional Structures (N–i–p)mentioning
confidence: 99%